Treatment of posttraumatic hemobilia in penetrating abdominal wound injury - Shafran, U. Mohamed; Konstantin, Belyuk; Sergeevich, Shilo Ruslan; Hafeel, F. Aysha; Thilakarathna, Nethmi R.; Vasilchuk, L. F.; Soroka, O. S. (International Journal of Research in Medical Sciences, 2025)
This case report details a rare occurrence of traumatic hemobilia in a 29-year-old male following a penetrating stab wound to the abdomen. After initial surgical treatment, the patient developed severe right hypochondrial pain, prompting further investigation that revealed hemobilia. Magnetic resonance imaging (MRI) showed a blood-filled gallbladder and thrombotic masses obstructing the hepatic ducts, leading to a laparotomy that confirmed a liver wound with hemobilia. Postoperative complications included hemorrhagic drainage from the common bile duct, which was addressed through selective angiography that identified a false aneurysm in the liver artery. Successful angioembolization achieved hemostasis, allowing for a smooth recovery without further invasive procedures. This case highlights the effectiveness of X-ray endovascular methods in managing traumatic hemobilia, demonstrating their minimally invasive nature, quicker recovery times, and reduced complications. It advocates for the integration of endovascular techniques in complex trauma management to improve patient outcomes.